2021
DOI: 10.1101/2021.01.07.425801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibrinolysis influences SARS-CoV-2 infection in ciliated cells

Abstract: Rapid spread of COVID-19 has caused an unprecedented pandemic worldwide, and an inserted furin site in SARS-CoV-2 spike protein (S) may account for increased transmissibility. Plasmin, and other host proteases, may cleave the furin site of SARS-CoV-2 S protein and γ subunits of epithelial sodium channels (γ ENaC), resulting in an increment in virus infectivity and channel activity. As for the importance of ENaC in the regulation of airway surface and alveolar fluid homeostasis, whether SARS-CoV-2 will share an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Co-expression and upregulation of PLAU, TMPRSS2, and ACE2 was observed in airway epithelial cells from severe/moderate patients and SARS-CoV-2 infected cell lines. This, together with a plasmin-mediated cleavage, could make cells more susceptible to infection (93). Interestingly, we also observed an enhanced expression of PLAU in nasal epithelium from severe cases when compared to mild and controls, highlighting the crosslink between both tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Co-expression and upregulation of PLAU, TMPRSS2, and ACE2 was observed in airway epithelial cells from severe/moderate patients and SARS-CoV-2 infected cell lines. This, together with a plasmin-mediated cleavage, could make cells more susceptible to infection (93). Interestingly, we also observed an enhanced expression of PLAU in nasal epithelium from severe cases when compared to mild and controls, highlighting the crosslink between both tissues.…”
Section: Discussionsupporting
confidence: 51%
“…First of all, the increased transmissibility of Covid-19 is caused also by an inserted furin site in SARS-CoV-2 spike (S) protein, that is cleaved during virus entry. Recent data show that plasmin is able to cleave the S protein furin site, thus favoring SARS-CoV-2 infection ( Hou et al, 2021 ). Second, the Covid-19 patients often suffer from a prothrombotic state associated to severe coagulopathies, that is not fully investigated.…”
Section: Bacterial and Viral Infectionsmentioning
confidence: 99%
“…Another analysis of bulk BALF transcriptomes also demonstrated PLAUR downregulation in COVID-19 patients [ 51 ]. A more in-depth single-cell transcriptomic study of BALF by Hou et al, however, revealed that PLAU expression is strongly upregulated in severe COVID-19 cases as compared to healthy controls [ 53 ]. To resolve these controversies, here, we compared single-cell transcriptomic data obtained from warm postmortem lung biopsies of patients diseased from COVID-19-associated pneumonia and lung biopsies from individuals with pulmonary fibrosis and control samples from healthy donors [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%